Multi-scale Structural Characteristics and Efficiency Analysis of Proton Exchange Membrane Water Electrolysis Hydrogen Production Technology - Chen Yu; Wu Hao; Zou Lintong (MATEC Web of Conferences)
Driven by the global energy transition and carbon neutrality goals, proton exchange membrane water electrolysis (PEMWE) technology has become the core technology for large-scale hydrogen production due to its advantages of high efficiency (74%-87%), fast response (millisecond level), and high-purity hydrogen production (99.999%). However, the industrialization process is limited by key bottlenecks such as the high cost of precious metal catalysts, the high cost of titanium-based bipolar plates, and the system investment cost. Based on the multi-scale analysis framework, we proposed a gradient catalytic layer design to reduce the precious metal load by 30%-50%, an ultra-thin proton exchange membrane (<50μm) to optimize the mechanical and chemical stability, and a three- dimensional corrugated flow field structure to reduce the two-phase flow resistance by 20%-35% and improve the current density uniformity by 40%. The research results provide a theoretical basis and technical solution for breaking through the cost and efficiency bottleneck of PEMWE technology, and promote its large-scale commercial application.